Kebijakan Pemerintah Daerah Dalam Pembinaan Prestasi Atlet - Frederika Rahanra; Tarsisius Sarkol (Univiversitas Dr. Djar Wattiheluw, 2022)
Sports problems seen in Southeast Maluku Regency, namely government policies have not touched the substance of sports development. This writing focuses on coaching athlete achievement. This study aims to evaluate government policies in fosteringathlete achievement in Southeast Maluku district. The population in this study were the KONI administrators of Southeast Maluku Regency and the Sports Manager of the Athletics Branch of Southeast Maluku Regency. This research will be analyzed descriptively qualitatively. The results of the study show that the coaching of athletes, coaches and sports branch managers is inconsistent, the availability of sports infrastructure is still minimal, the budget allocation is limited each year, the coaching money is not accompanied by consistent assistance. Therefore, it is recommended that the Southeast Maluku district government and the local KONI Management, as well as the Sports Branch Management are more consistent in coaching athletes and coaches to achieve achievements.